2019
DOI: 10.3390/foods8100519
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, Textural, Sensory Properties and Quality of Wheat–Yam Composite Flour Noodles

Abstract: Herein, feasibility of supplementing wheat flour with Chinese yam powder (CYP) for noodle preparation was assessed. After supplementation with CYP, the alterations in chemical, texture, cooking, rheological, and microstructure attributes of noodles were observed. Due to higher protein and lower gluten, 20% of CYP promoted the stable network of gluten and starch particles. However, the excessive addition reduced the flexibility and the chewiness. The adverse changes were observed at 40% substitution level in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…The findings from the both cohesiveness of the fried wheat cocoyam noodles with defatted soya bean flour and the fried wheat–cocoyam noodles without defatted soya bean flour disagrees with studies from Sun et al. (2019) with similar studies who reported to that Chinese yam flour had no significant difference on the wheat–Chinese yam noodles cohesiveness.…”
Section: Resultscontrasting
confidence: 72%
“…The findings from the both cohesiveness of the fried wheat cocoyam noodles with defatted soya bean flour and the fried wheat–cocoyam noodles without defatted soya bean flour disagrees with studies from Sun et al. (2019) with similar studies who reported to that Chinese yam flour had no significant difference on the wheat–Chinese yam noodles cohesiveness.…”
Section: Resultscontrasting
confidence: 72%
“…The higher cooking loss obtained in this study for pasta enriched with GP can be attributed to the polymer interactions in the gluten matrix and/or to the competition of proteins for water, leading to starch loss [ 44 ]. A similar trend of cooking loss was reported for fettuccini pasta supplemented with grape marc [ 5 ] and can be due to the dietary fiber content of the added ingredient.…”
Section: Discussionmentioning
confidence: 99%
“…The tensile strength and elasticity distance are two important properties of noodles [ 50 ]. The elasticity strength relates the toughness of the noodles, and the tensile distance represents the ductility of noodles.…”
Section: Resultsmentioning
confidence: 99%